Przejrzystość i targetowanie reklamy politycznej w prawie Unii Europejskiej - Sławomir Dudzik (Politeja)
The aim of the article is to analyze and assess the effectiveness of actions taken by the European Union in recent years to counteract disinformation and various forms of manipulation of public opinion, with particular emphasis on the legal provisions adopted in 2024 regarding transparency and targeting of political advertising. The paper focuses primarily on substantive legal solutions, leaving aside organizational and procedural issues. It indicates that the provisions of Regulation 2024/900 strengthen the protection of the EU citizens’ rights, especially towards international media companies operating in the political advertising market and with the political entities themselves. They also create additional safeguards against external interference in EU elections and referendums. The degree of transparency of political advertising required by the provisions of Regulation 2024/900 was assessed positively. However, there are concerns about the possibility (limited) of using targeting techniques and advertising delivery using sensitive data in political advertising in Regulation 2024/900.